A 16-Year-Old Female with Diabetic Ketoacidosis, Diabetes Mellitus, Sepsis, and Constipation: A Case Report - Anggun Febry Kurniasari; Nuri Susanti (Heca Sentra Analitika, 2026)
Diabetic ketoacidosis (DKA) is a serious and potentially fatal complication of hyperglycemia, with a reported mortality rate of 2–5% depending on age. It commonly occurs in patients with uncontrolled insulin-treated diabetes mellitus (DM), especially when accompanied by severe underlying illness. Infection and insulin withdrawal are the two main triggers of DKA, with bacterial infections accounting for approximately 50% of cases, including urinary tract infections, pneumonia, and gastrointestinal conditions such as constipation. Constipation is more prevalent in diabetic patients with colonic neuropathy and may further complicate clinical outcomes. This case report presents a 16-year-old female with suspected new-onset type 1 DM who was admitted with DKA complicated by severe constipation and sepsis. The case highlights the complex interaction between poor glycemic control, infection, and systemic inflammatory responses in DKA. Diabetes mellitus can alter immune responses, infection patterns, and sepsis outcomes, contributing to increased morbidity and mortality. Diagnosing infection in patients with DKA remains challenging because both conditions share overlapping clinical and laboratory features, including fever, leukocytosis, and systemic inflammation. Early identification of bacterial infection is essential to ensure prompt and appropriate treatment while avoiding unnecessary antibiotic use that may contribute to antimicrobial resistance. This case report emphasizes the importance of early diagnosis of concurrent infection in patients with DKA to enable prompt management and improve clinical outcomes.